Front Cover. Issue 11 (6th November 2019) - Brandes, Ursula; Furevik, Beate Beatriz; Nielsen, Lene Rostgaard; Kjær, Erik Dahl; Rosef, Line; Fjellheim, Siri
Abstract : The cover image is based on the Original Article Introduction history and population genetics of intracontinental scotch broom (Cytisus scoparius) invasion by Siri Fjellheim et al., https://doi.org/10.1111/ddi.12979 .